Artificial Intelligence in Marketing Analytics: The Application of Artificial Neural Networks for Brand Image Measurement - Nufer, Gerd; Muth, Manuel (Journal of Marketing Development and Competitiveness, 2022)
Addressing the high complexity of brand image measurement, the present research paper investigates the use of artificial neural networks in this particular application context. Since profound insights into the image of a brand are essential for management, the deployment of this learning algorithm is considered as it allows modeling of complex non-linear and multilayered relationships. The conceptual approach presented in the paper is illustrated with the empirical example of the sportswear manufacturer adidas. By using quantitative survey data, a multilayer artificial neural network is created to link the evaluations of specific brand attributes with the overall evaluation of the brand. Based on an analysis of the connection weights between neurons of the artificial neural network, the importance of different brand attributes for the brand evaluation is quantified. This results in concrete implications for brand management practice and potential for further investigations on the use of artificial intelligence in marketing analytics.